PELUANG PENERAPAN PRODUKSI BERSIH PADA KAWASAN INDUSTRI PERIKANAN MUNCAR KABUPATEN BANYUWANGI JAWA TIMUR - Lestario Widodo (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Coastal areas in Muncar Banyuwangi has developed one of the largest fisherys industry centers in Indonesia. Fisherys industry in the production process using a fish as a main input and also need a lot of clean water. The impact of these activities is the occurrence of environmental pollution in the form of liquid waste and the unpleasant smell. Cleaner produktion is minimization of waste from source. The application of cleaner production with its assessment and identification to production process will create any innovations. In the cleaner production method contains several strategies that can be implemented forreducing and minimizing of industrial waste including prevention, recycling, treatment and disposing. One of prospective instruments that can be developed further in the industrial implementation of cleaner production is fisherys industry at Muncar Banyuwangi. The main opportunities to implementation of cleaner production, especially in stages using excessive water in the process of weeding and cleaning fish, stage of the main raw material the use of fish by re-sorting a more effective, and efficient charging process scattered on the tin.Key words : Cleaner production, fisherys industry